(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
Dedicated to modern strategies for developing students’ cognitive competencies. It describes interactive methods that increase the level of students’ critical thinking and ensure the deep assimilation of educational material. The research results are of practical importance for secondary school teachers and researchers in the field of pedagogy.